Nomograms for predicting the prognosis of patients with penoscrotal extramammary Paget’s disease: A retrospective study in the SEER database and two medical centers - Song, Le-Bin; Zhou, Xiang; Luan, Jiao-Chen; Wang, Hao-Yang; Cao, Xue-Chen; Lu, Jia-Wei; Zheng, Yu-Jie; Wu, Xin-Feng; Lu, Yan (Frontiers in Oncology, 2022)
Background: Extramammary Paget’ s disease (EMPD) is a rare cutaneous malignant tumor, and the prognostic factors associated with penoscrotal EMPD remains unclear. The purpose of this study is to investigate prognostic factors and construct nomograms to predict the outcome of patients with EMPD located in the penis or scrotum. Methods: From the Surveillance, Epidemiology and End Results (SEER) database, we extracted 95 patients with primary EMPD located in the penis or scrotum as the training cohort. Forty-nine penoscrotal EMPD patients were included from two medical centers as the external validation cohort. Univariate and multivariate Cox regression model were applied to investigating risk factors of cancer-specific survival (CSS) and overall survival (OS). Based on the results of multivariate Cox regression analysis, the nomograms were constructed for predicting CSS and OS of patients with penoscrotal EMPD. The concordance index (C-index), receiver operating characteristic (ROC) curves and calibration curves were applied to evaluate the practicability and accuracy of the nomograms. Results: In the training cohort, multivariate Cox regression analysis showed that marital status and tumor stage were independent factors of CSS, and marital status, tumor stage and surgery are associated with OS independently in patients with penoscrotal EMPD. Based on these results, we developed nomograms to predict CSS and OS respectively. The C-index values were 0.778 for CSS, and 0.668 for OS in the training set, which displayed the good discriminations. In the external validation set, the C-index values were 0.945 for CSS, and 0.703 for OS. The areas under the curve (AUC) values of nomogram predicting 1-, 3-, and 5-year CSS were 0.815, 0.833, and 0.861 respectively, and 0.839, 0.654, and 0.667 for nomogram predicting 1-, 3-, and 5-year OS respectively. In the validation set, the AUC values of nomogram predicting 1-, 3-, and 5-year CSS were 0.944, 0.896, and 0.896 respectively, and 0.777, 0.762 and 0.692 for nomogram predicting 1-, 3-, and 5-year OS respectively. Additionally, the internal calibration curves also proved that our nomograms have good accuracy. Conclusions: By incorporating marital status, tumor stage and/or surgery, our nomograms can efficiently predict CSS and OS of patients with penoscrotal EMPD.